Primacy of Arabic Poetry: An Anthropological Cultural Study - Hashim, Nibras (Al-Adab Journal, 2021)
This research tackles the anthropological significance of the beginnings of Arabic poetry as a cultural study of its written phase. The cultural studies as well as the cultural anthropological studies are concerned with whatsoever man produces away from heredity. Culture is an evolving structure rather than a static one that is passed from one generation to another. Hence, in studying the culture of a certain people at a given time period care should be given to the manifestations of this structure; i.e., the cultural processes of producing meaning. This requires an investigation in the everyday popular culture or literature; the commonplace rather than the canonical or mainstream literature which produces meta-narratives that do not reveal the individuals’ activities of everyday life; these manifestations are fixed concepts that have been formed by a collective elite consciousness. It can be said that the "Arajeez" (Arabic plural for "Erjooza" which is a poem that follows the "rajaz" meter) or the verses that represent the beginnings of Arabic poetry had suffered marginalization and elimination at the early stage of writing the Arabic culture as they had been compared to the literature of the elite or the high literature which is artistically and linguistically more mature; it is the literature of the markets of Mecca. Another point should be made, these arajeez were eliminated by scholars and linguists during their endeavors to put grammatical and critical rules, as a rule is built on what is common, familiar, and standard rather than on what is peculiar and uncommon. Those texts had been improvised spontaneously and were not subjected to artistic or thematic polish or standardization. They articulated daily practices and were not an elite literature. Those verses or poems started with the activity of the first Arab Bedouins in the desert (with the desert- guide or camel-rider). They represented the early beginnings of founding a collective Arabic consciousness when Arabs started their first steps of gathering in groups and communities and then of integrating into tribes with abstract intellectual bondages which were shared among tribe members and that enhance their existence. Poetry was a manifestation of these bonds, being a metrical parole that is easy for memory to "carry" every time they travel in search for water and grass. Early poetry was a spontaneous art produced on the spot. However, it revealed reflections on abstract concepts which were ahead of their time like, for instance, the concept of time as, in spite of the primitivism of their life-style, Bedouins realized that it is time that defeats man, so they tried to transcend it by their linguistic skills through the ability to come up with an artistic expression that is immortalized after their death. The investigation of those artistically primitive texts is significant as they constitute man’s cultural identity. Cultural identity is formed by everything the individuals produce like legends, popular tales, spontaneous arts, and so on; away from the categories of high and low, central and peripheral, elite and common. And the bigger the collective cultural repertoire among individuals is, the more solid identity those individuals have; an identity that gathers them and that firstly expresses itself, and secondly, distinguishes itself from other identities by avoiding dissolve and imitation. It is an identity that rests on a cultural reserve what makes it able to be itself every time it comes into contact with the Other.